KEWENANGAN PEMERINTAHAN DAERAH TERHADAP PELAKSANAAN PELEPASAN TANAH ADAT DI KABUPATEN MERAUKE - Julianto Jover Jotam Kalalo (Universitas Musamus, Merauke, Papua, 2015)
Legal actions by governments can be either setting or set, which is a legal act of the government public-sided or unilateral (eenzijdige publiekrechtelijke handeling) binding or generally applicable in accordance with the legislation that became the basic settings. Governmental authority in the land sector may be delegated by the government to local government. Status of the Local Government act as enforcers state that is not genuine because it was given (outsourced) authority to it by the Central Government. Local authorities in the land sector stipulated in Government Regulation No. 38 of 2007 on government affairs division between the Government, Provincial Government and Local Government / town. In the government regulation authority given to the government of the provincial and district / city in terms of communal land is the establishment of communal land, this is done through the establishment of local regulations. The purpose of this study is to know about the implementation of regional autonomy and ap customary land release in Merauke.This research is a normative law. This study uses several approaches to obtain information on the issues raised, among others, the approach of the law (statute approach), approach the concept (conceptual approach), the historical approach (hisrorical approach) and the philosophical approach (philosophy approach). This type of research is qualitative research using this type. Data analysis techniques used in legal research is the analysis of qualitative data, which is a procedure for research that produces descriptive data analysis.The study concluded local government authority is the formal power that comes from the law, but local governments do not have full power to the release of customary land but customary law which have full power to the release of customary land.